Spouses as Home Health Workers and Cooks: Insights for Applied Research - Shoshana Grossbard (Institute of Labor Economics (IZA), 2023)
This paper presents a model of consumption and household production that takes into account substitution between health-related goods that are produced at home and those produced commercially as well as substitution between goods produced at home by oneself and those produced by one's spouse or partner. New insights are offered that help interpret heterogeneity analysis in data for couples, when individuals differ by gender, age, weight and education. The model also identifies new variables related to marriage markets that could help explain consumption, including demand for medical care and good nutrition. These variables include sex ratios (and exogenous parameters that influence sex ratios) as well as legal changes related to marriage and divorce. A reexamination of the determinants of the price elasticity of demand includes an explanation for gender gaps in such elasticity.
Keywords: D1; D11; D13; I1; I12; J12; 330; health; caregiving; marriage; consumption; household production